Detection of Hepatitis B Virus (HBV) Genotypes by Sequence in Diyala Province - Marwa Hadi Mustafa, Zahraa Jaafar Jameel (Pakistan Journal of Medical & Health Sciences, 2022)
Background: To put it simply, hepatitis is liver inflammation. Hepatitis B virus (HBV) infection is a public health problem because it can lead to serious liver conditions like hepatocellular carcinoma and cirrhosis. Ten HBV genotypes (A-J) were distinguished based on viral sequence similarity. Objective: detection of HBV utilizing polymerase chain reaction (PCR) technique, followed by viral nucleotide sequence and phylogenetic analysis. Methods: A cross-sectional study was conducted in170 reviewers (103 males and 67 females) who attended the Baquba Teaching Hospital, Teaching Laboratories, the Main Blood Bank, and Baladrooz General Hospital. Age ranging 13-75 years. The samples were collected from Diyala Province of Iraq; person data was collected by using questioner, including their name, age, gender, address, academic achievement, source of infection, take vaccine of HBV, and corona infection. Enzyme-linked immune sorbent assay test (ELISA) was used to detect hepatitis B surface antigen (HBsAg) in serum. Amplification Polymerase Chain Reaction (PCR) of HBV p gene of serum samples was performed to detect HBV from serum samples. The sequence of the PCR products of the polymerase gene was sent for Sanger sequencing using ABI3730XL, an automated DNA sequencer, by Macrogen Corporation – Korea for the study of mutations and genotype identification. The results were received by email and then analyzed using geneious software. Results: The positive samples of HBV by ELISA were 70 (41.20%), and 100 (58.80%) samples were negative. While positive samples for HBV-DNA PCR were 14 (8.20%). When compared the sequence of local isolates with NCBI-Blast Hepatitis B virus showed that all isolates were D genotype. Variation result showed that the highest type of mutation was Transition when compared with the NCBI referring sequences. Statistically: The present study revealed there was a significantly different (p<0.05) in the positivity of HBV detected by ELISA and PCR between study groups. Additionally, there was a significantly different (p<0.05) between the positivity of HBV detected by ELISA and PCR and age groups, gender, Social status, address, education , jaundice infection of patients, the HB vaccination, and infection source of patients. Keywords: HBV, ELISA, PCR, Sequence, Variation, Phylogenetic Tree, Diyala, Iraq.